Otimização e análise mecânica de pastas geopoliméricas para uso em poços sujeitos à injeção cíclica de vapor - Paiva, Maria das Dores Macedo (2008)
Oil wells subjected to cyclic steam injection present important challenges for the development of well cementing systems, mainly due to tensile stresses caused by thermal gradients during its useful life. Cement sheath failures in wells using conventional high compressive strength systems lead to the use of cement systems that are more flexible and/or ductile, with emphasis on Portland cement systems with latex addition. Recent research efforts have presented geopolymeric systems as alternatives. These cementing systems are based on alkaline activation of amorphous aluminosilicates such as metakaolin or fly ash and display advantageous properties such as high compressive strength, fast setting and thermal stability. Basic geopolymeric formulations can be found in the literature, which meet basic oil industry specifications such as rheology, compressive strength and thickening time. In this work, new geopolymeric formulations were developed, based on metakaolin, potassium silicate, potassium hydroxide, silica fume and mineral fiber, using the state of the art in chemical composition, mixture modeling and additivation to optimize the most relevant properties for oil well cementing. Starting from molar ratios considered ideal in the literature (SiO2/Al2O3 = 3.8 e K2O/Al2O3 = 1.0), a study of dry mixtures was performed,based on the compressive packing model, resulting in an optimal volume of 6% for the added solid material. This material (silica fume and mineral fiber) works both as an additional silica source (in the case of silica fume) and as mechanical reinforcement, especially in the case of mineral fiber, which incremented the tensile strength. The first triaxial mechanical study of this class of materials was performed. For comparison, a mechanical study of conventional latex-based cementing systems was also carried out. Regardless of differences in the failure mode (brittle for geopolymers, ductile for latex-based systems), the superior uniaxial compressive strength (37 MPa for the geopolymeric slurry P5 versus 18 MPa for the conventional slurry P2), similar triaxial behavior (friction angle 21° for P5 and P2) and lower stifness (in the elastic region 5.1 GPa for P5 versus 6.8 GPa for P2) of the geopolymeric systems allowed them to withstand a similar amount of mechanical energy (155 kJ/m3 for P5 versus 208 kJ/m3 for P2), noting that geopolymers work in the elastic regime, without the microcracking present in the case of latex-based systems. Therefore, the geopolymers studied on this work must be designed for application in the elastic region to avoid brittle failure. Finally, the tensile strength of geopolymers is originally poor (1.3 MPa for the geopolymeric slurry P3) due to its brittle structure. However, after additivation with mineral fiber, the tensile strength became equivalent to that of latex-based systems (2.3 MPa for P5 and 2.1 MPa for P2). The technical viability of conventional and proposed formulations was evaluated for the whole well life, including stresses due to cyclic steam injection. This analysis was performed using finite element-based simulation software. It was verified that conventional slurries are viable up to 204ºF (400ºC) and geopolymeric slurries are viable above 500ºF (260ºC)